Breastfeeding and SARS-CoV-2 - Bastidas-Pacheco, Gilberto (2022)
Breastfeeding is the normative standard for infant nutrition and ideal in pandemics such as that caused by SARS-CoV-2 as it is the cleanest and safest way to nourish infants and young children. The objective of this writing is to unveil the existing information on maternal-infant vertical transmission of the new SARS-CoV-2 coronavirus. It was a documentary review of information extracted from digital databases using descriptors. The data obtained were analyzed and shown in this research in two sections: breastfeeding and SARS-CoV-2 and conclusions. It is concluded that breastfeeding should begin as soon as possible and that skin-to-skin contact should not be interrupted, since vertical transmission has not been demonstrated.